Public Perceptions About Pawning Gold at Sharia Pawnshops (Study of Sharia Pawnshops, Setia Budi Branch Medan) - Fiqkri Ardian; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
The title of this the public perception about pawning gold of pegadaian syariah. The purpose of the research is to determine the extent to which understanding of the public about process of pawning gold to give by Pegadaian Syariah. The date used in this research are primary data and secondary data. The collecting of the primary data is done by giving the questionnaire to the customer of Pegadaian Syariah. While the secondary data are obtained from Pegadaian Syariah, books, literature, internet and others. The analysis method that used in this research is descriptive analysis using SPSS 16,0 version. The result of this research understanding customer’s or community about pawning gold is various. No one understand anyone not understands. But my observation, that has become a permanent customer’s of Pegadaian Syariah understanding about pawning gold to given and they have opinion about how to pawn gold of Pegadaian Syariah very easy and not many requirements.